Biostimulants in the growth and yield of Phaseolus vulgaris L. in Northern Sinaloa - Romero-Félix, Celia Selene; Pellegaud-del Paso, Damaris Fabiola; Salas-Arellanes, Juan Antonio; Sauceda-Acosta, Raúl Hipólito; Buelna-Tarín , Salomón; López-Valenzuela, Blanca Elvira (Ecosistemas y Recursos Agropecuarios, 2023)
At the national level, the state of Sinaloa is the largest producer of bean crop (Phaseolus vulgaris L.), therefore, the use of biostimulants for its production is being implemented to reduce the use of chemical fertilizers and to contribute in a friendly way to the environment. The objective of this study was to evaluate the effect of the mycorrhizae Glomus intraradices (M), free amino acids (AA) and the combination M +AAon the growth of the aerial part of the plant and the yield and its components in bean variety Azufrado Higuera under field conditions in northern Sinaloa. A randomized block design with three repetitions was used: T1) AA; T2) M; T3) the combination M+AA, and T4) control. The growth of the aerial part of the plant and the yield were higher with the M+AA treatment.
Keywords: Mycorrhiza; aminoacids; yield components; foliar area; dry weight